Legal Protection of Famous Brand Rights (Well-Known Mark) Starbucks (Studi Putusan Mahkamah Agung Nomor 836 K/PDT.SUS-HKI/2022) - Marchelya*, Vanya; Rahaditya, R. (Universitas Syiah Kuala, 2023)
The case pertaining to the disagreement between Starbucks Company and PT Sumatra Tobacco Trading Company was resolved at the cassation level by Supreme Court Decision Number 836 K/PDT.SUS-HKI/2022, and at the first level by Commercial Court Decision Number 51/Pdt.Sus/Merek/2021 /PN. Where the conflict arose from the complaint filed in class 34 against PT Sumatra Tobacco Company to cancel the use of the